Optimizing Aluminium 6061 Turning using Kesambi Oil-Based Cutting Fluid and Response Surface Methodology to Reduce Surface Roughness - Wahjudi, Ari; Baihaki, Raihan; Anam, Khairul (Universitas Negeri Malang, 2025)
This study investigates the viability of Kesambi oil (Schleichera oleosa) as an environmentally sustainable, bio-based cutting fluid to reduce surface roughness during the turning of Aluminium 6061. The study employs Response Surface Methodology in conjunction with a Central Composite Design to identify the optimal parameter combination between two primary variables, including the composition of Kesambi oil and the depth of cut during machining. The best configuration, comprising 19.57% Kesambi oil and a cutting depth of 0.99 mm, yielded a surface roughness of 3.61 µm, closely matching the predicted value of 3.59 µm. A Fourier Transform Infrared Spectroscopy was conducted to indicate the presence of a thin lubricating film on the surface. This film can reduce the friction and enhance the high surface quality. Generally, the results show that Kesambi oil is effective and sustainable compared to conventional petroleum-based cutting fluids.